Questioning Copernicus: cosmological principles on the eve of the Scientific Revolution - Tessicini, Dario (Journal of physics. Conference series, 2024)
This paper examines the issues arising from Nicolaus Copernicus’s heliocentric theory when it is considered in the context of historical controversies over the planetary order. It will investigate the terms of this issue as they were available to Copernicus, and will stress both continuities and discontinuities with Ptolemaic astronomy. The consequences of heliocentrism for celestial physics will also be considered. Some of the consequences are inherent to heliocentrism, although not all of them were accounted for in De revolutionibus and certain outcomes may have been unforeseen by Copernicus or discordant with his theory.